Talking Animals: Explorations in an Indian Literary Genre - Olivelle, Patrick (Religions of South Asia, 2013)
Animals are certainly good to think (bonnes a penser), as famously noted by Claude Levi-Strauss, but from the dawn of literature humans have also given them voices so that they can participate vicariously in an anthropomorphized animal linguistic and social world paralleling the human, giving rise to the literary genre of the animal fable. The earliest use of animals in literature was probably as similes. Such allegories abound in the earliest strata of the Rg-Veda. What is interesting in these comparisons for later animal tales is that a particular characteristic is singled out as defining a particular animal and constituting its very nature (svabhava). The association of a particular species with a set of moral and intellectual qualities, with personality traits, plays a central role in later animal fables. But what about talking animals? When do they make their first appearance in the extant corpus of Indian literature? This article will reflect on the religious and cultural backdrop within which the anthropomorphizing habit of Indian animal tales took place in Indian Sanskrit literature.